Impact of corporate identity on reputation and employer’s brand - Charvat Janechova, Jana; Bednárik, Jaroslav (Serbian Journal of Management, 2023)
The study focuses on the area of ​​corporate identity and its correlation to reputation and employer’s brand. As competition in the labor market grows, more companies, in particular, are investing their efforts and resources in employer brand development that would be attractive to both current and potential employees. If the organization wants to be perceived as a desirable place for work and the employer as ideal, consistent corporate communication and harmonization of internal, employee-to-employee and external-employee-to-employee communications are required. The purpose of the paper is to examine the conditions under which it is possible to create a good reputation and an attractive employer brand through corporate identity and thus gain a competitive advantage in the labor market. Our interest is to determine what attributes need to be met to create an attractive brand for an employer with a good reputation.
Keywords: corporate identity, employer’s brand, employer, employees, reputation; korporativni identitet, brend poslodavca, poslodavac, zaposleni, reputacija